Kelembagaan pendukung agroforestry bambu di Rajadesa - Eva Fauziyah; Tri Sulistyati Widyaningsih; Devy Priambodo Kuswantoro (Jurnal Agroforestri Indonesia, 2021)
The use of bamboo for construction and various products is increasing as part of an environmentally friendly lifestyle. This effort needs to be supported by bamboo cultivation and strong institutions. This study aims to identify and analyze the institutions that play a role in the development of bamboo agroforestry. The research was conducted from 2016 to 2021 in West Java. Data were collected through interviews with actors related to bamboo development, meetings, Focus Group Discussion (FGD), observation and documentation. The data were analyzed and presented descriptively. The results show that the supporting institutions of bamboo development consist of national institutions and local institutions. National institutions include the Ministry of National Development Planning, Ministry of Environment and Forestry, Indonesian Institute of Sciences, Ministry of Industry, Ministry of Public Works and Public Housing (PUPR), Academy of Bambu Nusantara, Research Center for Bamboo Udayana University, and PT Charta Putra Indonesia. Local institutions include farmers, farmer groups(Karya Mukti II), woman farmer groups, craftsman group (BASUKA), research team of Research and Development of Agroforestry Technology Institute (BP2TA), extension workers, Sukaharja Village Government, bamboo business actors, Industry and Trade Office of Ciamis District, Industry and Trade Office of West Java Province, Branch Region VII of Forestry Service, ta'lim assemblies, and middleman. Each institution plays a role according to its main duties. The bamboo development program at the national level is synergized by the Ministry of National Development Planning while the program at the local level is synergized by the BP2TA research team in collaboration with the Sukaharja Village government. The institutions synergies allow the development of bamboo to be carried out comprehensively.